The extent of marketing capability and market orientation in franchise business in Malaysia - Md Isa, Filzah; Hoe, Chee Hee; Othman, Siti Norezam; Din, Mohd Salleh; Mohd Harif, Mohd Amy Azhar; Hussin, Zolkafli; Md Jani, Mohamad Yusop (Centre for Promoting Ideas, 2012)
The purpose of this study is to provide a deeper insight and understanding into issues surrounding that impact the success of franchisors in Malaysia.In this paper, the researchers explore the role and extent of marketing capability and market orientation concept applied by Malaysian franchisors especially the Muslim entrepreneurs, in developing and operating their franchise businesses.In doing so, the critical success factors (CSFs) of franchisors will be identified and then confirmed using three methods of qualitative study: convergent interview, confirmatory workshop and secondary information. The case study approach involves a series of in-depth interviews with several predetermined local franchise entrepreneurs (franchisors) who have proved to be successful in their business operations and who actively play a dominant role in the industry.The information gathered from this study is useful in forming guidelines for the success of business operators in franchising.